General problems of development and implementation of nanomaterials and nanotechnologies - Yu. A. Nikalaichyk; D. V. Kuis; N. A. Svidunovich; S. L. Rovin (Литьë и металлургия)
This article is the first in a cycle devoted to the creation and application of nanomaterials and technologies in modern industry, in general, and in metallurgy, materials science and foundry, in particular. The article discusses the unique properties of nanomaterials and the associated advantages, disadvantages and areas of their application, as well as the problems and directions of the development of nanotechnologies, the prospects and consequences of the widespread use of nanomaterials in various fields, their influence on the development of society, industry, economy and ecology.